Aflatoxin Proficiency Testing and Control in Africa (APTECA) - Herrman, Tim; Muiruri, Anne (2019)
Tim Herrman and Anne Muiruri WEBINAR Catalyzing the Use of Aflatoxin Control Technologies in Kenya and Ghana NOV 26, 2019 - 09:00 AM TO 11:00 AM EST